Adjusting to the pandemic: Remote support for professionals working with asylum seekers. (1st December 2021) - Govoni, Devon; Ramirez, Kelvin; Rubesin, Hillary
Three expressive arts therapists from the volunteer group, Voces Arts and Healing, review and reflect on virtual mentorship and supervision provided to mentees working on the ground in Juarez, Mexico, as the immigration crisis at the border persisted and the COVID-19 pandemic was declared around the globe. The Migrant Protection Protocol (MPP) programme is briefly explained along with implications it posed on the duelling crises. Compassion fatigue, vicarious trauma, burnout and aspects of supervision and art-based supervision are examined within the contexts of these international concerns.